Nonnegative periodicity on high-order proportional delayed cellular neural networks involving $ D $ operator - Guo, Xiaojin; Huang, Chuangxia; Cao, Jinde (AIMS mathematics, 2021)
This paper aims to deal with the dynamic behaviors of nonnegative periodic solutions for one kind of high-order proportional delayed cellular neural networks involving $ D $ operator. By utilizing Lyapunov functional approach, combined with some dynamic inequalities, we establish a new assertion to guarantee the existence and global exponential stability of nonnegative periodic solutions for the addressed networks. The obtained results supplement and improve some existing ones. In addition, the correctness of the analytical results are verified by numerical simulations.